Evaluation of human bone marrow stromal cell growth on biodegradable polymer/bioglass composites. - Yang, X; Webb, D; Blaker, J; Boccaccini, A; Maquet, V; Cooper, C; Oreffo, R (2006)
Bone tissue engineering using human bone marrow mesenchymal stem cells (HBMCs) and biocompatible materials provides an attractive approach to regenerate bone tissue to meet the major clinical need. The aim of this study was to examine the effects of novel porous biodegradable composite materials consisting of a bioactive phase (45S5 Bioglass, 0, 5, and 40 wt%) incorporated within a biodegradable poly(dl-lactic acid) matrix, on HBMCs growth. Cell adhesion, spreading, and viability was examined using Cell Tracker Green/Ethidium Homodimer-1. Bone formation was assessed using scaffolds seeded with stro-1 positive HBMCs in nude mice. In vitro biochemistry indicated that with minimal scaffold pre-treatment osteoblast activity falls with increasing Bioglass content. However, 24h scaffold pre-treatment with serum resulted in a significant increase in alkaline phosphatase specific activity in 5 wt% Bioglass composites relative to the 0 and 40 wt% Bioglass groups. In vivo studies indicate significant new bone formation throughout all the scaffolds, as evidenced by immunohistochemistry.